Stock market reaction: An investigation of COVID-19 effects in ASEAN Countries - Basyith, Abdul; Periansya, Periansya; Fitriya, Fitriya (International Journal of Finance Research, 2024)
This study examines the effects of the various COVID-19 announcements by the World Health Organization (WHO) on stock returns in ASEAN countries, which is different from previous research in that most of the research only observed the first announcement of COVID-19 when a pandemic was declared This study uses 6 announcements of COVID-19, starting from the first time COVID-19 was identified until it was declared a variant delta. The results revealed that the market reaction in ASEAN to the first announcement of COVID-19 in China on December 31st, 2019, shows a positive and non-significant abnormal return and cumulative abnormal return. On January 13th, 15th, 21st, and 24th, 2020, the market also reacted negatively but not significantly to the announcement of the first recorded case outside China, which is in Thailand, Japan, the USA, and the European region, and it was an intermittently negative reaction but not significant. On March 7th, 2020, when the confirmed cases surpassed 100,000 globally, and on March 11th, 2020, when WHO officially announced COVID-19 as a global pandemic, the ASEAN market reacted negatively and significantly for abnormal and cumulative abnormal returns, which is inconsistent with Salisu, Sikiru and Vo (2020) and Topcu and Gulal (2020). However, the ASEAN countries reacted positively but not significantly to the second wave announcement on May 31st, 2021.